Comparative Evaluation between Single Noncompression Miniplate and Two Noncompression Miniplates in the Treatment of Mandibular Angle Fractures. Issue 2 (June 2019) - Mondal, Shubhamoy; Singh, Gaurav; Mishra, Madan; Gaur, Amit; Srivastava, Abhinav
This study was conducted to compare the outcome of single noncompression miniplate versus two noncompression miniplates in the treatment of mandibular angle fracture. A total of 40 patients were divided into two groups: Group I ( n = 20), patients were treated by single miniplate at superior border of mandible by intraoral approach; Group II ( n = 20), patients were treated by one miniplate at superior border of mandible, intraorally, and another at the lateral aspect of angle, transbuccally by trocar and cannula. Comparative evaluation was done at 1, 2, 4, 6, and 12 weeks and 6 months. The findings of this study suggest that there was no significant difference in postoperative complications (malocclusion, pain, swelling, infection, facial nerve injury, wound dehiscence, plate exposure) and bite force between the two groups.